Highly functionalized calix[4]arenes via multicomponent reactions: synthesis and recognition properties. Issue 34 (24th June 2019) - Zadmard, Reza; Akbarzadeh, Ali; Jalali, Mohammad Reza
Abstract : Multicomponent reactions (MCRs) include several aspects of green chemistry principles, so it is obvious that chemists in different areas are increasingly interested in providing their product by multicomponent approaches. Abstract : Multicomponent reactions (MCRs) include several aspects of green chemistry principles, so it is obvious that chemists in different areas are increasingly interested in providing their product by multicomponent approaches. MCRs can be very useful in supramolecular chemistry, especially to produce novel supramolecular derivatives. Therefore, there are several reports of highly-functionalized calix[4]arene derivatives obtained by MCRs instead of conventional stepwise protocols during the last decade. In this paper, we have particularly focused on the exploitation of upper rim and lower rim substituted calix[4]arenes in multicomponent approaches as a facile and convenient synthetic strategy. The value of this method lies in its operational simplicity, mild reaction conditions and structural diversity of the products. Interestingly, in most cases the products afforded by this method offer unique features and applications which are highlighted in the following sections.